Peinando a una negrita: el estigma «del pelo» en la obra teatral de Victoria Santa Cruz Gamarra - Santa Cruz Bustamante, Alina Consuelo (2022)
This paper is a critical commentary on the script of a short piece of theater of Victoria Santa Cruz Gamarra titled Combing a Little Black Girl. In a first time we present the basis of the black theater of Victoria. This piece deals with the stigma of the hair. Victoria developed the facet of playwright from her beginning into the performing arts. She would define the objectives of her theatrical approach as a way to search for the understanding of our psychological processes (Instituto Nacional de Cultura, 1980). The actor can develop the ability to become aware of their own reactions to questions and conflicts originating in the past, for example in the case of Afro-descendants, in a colonial past of enslavement. It is then a tool that allows us to face the internal struggles that, because they continue to be rooted in society and in our own inner hearts, project a wrong vision of our future.